A Primary Intramuscular Hydatid Cyst of the Proximal Thigh : A Rare Case Report - Rahman, M Hafizur; Hossain, ASM Zakir; Islam, M Saiful; Khatun, Khodeza; Rahman, M Anisur; Chowdhury, M Sharif (TAJ: Journal of Teachers Association, 2018)
Primary intramuscular hydatid cyst of thigh is a very rare parasitic disease caused by Echinococcus granulosus. We present an unusual case of primary hydatid cyst in a 21-year old male who presented with slowly growing painless lump in the anteromedial aspect of proximal right thigh. Ultrasonography of the mass revealed a multiloculated cyst in the medial compartment of right proximal thigh without detectable primary any other location. MRI clearly displayed the lesion showing cystic mass with multiple well defined daughter cysts and diagnosis of hydatid cyst was made. The patient was treated surgically and cyst was excised. Macroscopic and microscopic histopathological examination confirmed the diagnosis of muscular hydatid cyst. Primary muscular hydatidosis is kept in mind in the differential diagnosis of a cystic mass of a skeletal muscle especially in endemic areas. TAJ 2011; 24(2): 142-144